Increased Risk of Interstitial Lung Disease in Children with a Single R288K Variant of ABCA3 - Thomas Wittmann; Sabrina Frixel; Stefanie Höppner; Ulrike Schindlbeck; Andrea Schams; Matthias Kappler; Jan Hegermann; Christoph Wrede; Gerhard Liebisch; Anne Vierzig; Angela Zacharasiewicz; Matthias Volkmar Kopp; et al. (BMC, 2016)
Abstract The ABCA3 gene encodes a lipid transporter in type II pneumocytes critical for survival and normal respiratory function. The frequent ABCA3 variant R288K increases the risk for neonatal respiratory distress syndrome among term and late preterm neonates, but its role in children's interstitial lung disease has not been studied in detail. In a retrospective cohort study of 228 children with interstitial lung disease related to the alveolar surfactant system, the frequency of R288K was assessed and the phenotype of patients carrying a single R288K variant further characterized by clinical course, lung histology, computed tomography and bronchoalveolar lavage phosphatidylcholine PC 32:0. Cell lines stably transfected with ABCA3-R288K were analyzed for intracellular transcription, processing and targeting of the protein. ABCA3 function was assessed by detoxification assay of doxorubicin, and the induction and volume of lamellar bodies. We found nine children with interstitial lung disease carrying a heterozygous R288K variant, a frequency significantly higher than in the general Caucasian population. All identified patients had neonatal respiratory insufficiency, recovered and developed chronic interstitial lung disease with intermittent exacerbations during early childhood. In vitro analysis showed normal transcription, processing, and targeting of ABCA3-R288K, but impaired detoxification function and smaller lamellar bodies. We propose that the R288K variant can underlie interstitial lung disease in childhood due to reduced function of ABCA3, demonstrated by decelerated detoxification of doxorubicin, reduced PC 32:0 content and decreased lamellar body volume.